Stress triggering mechanism of strong mine earthquake in huge thick strata revealed by inversion of joint source rupture information - Yao YANG; Anye CAO; Yaoqi LIU; Xianxi BAI; Changbin WANG; Chengchun XUE; Qiang WANG (Meitan xuebao)
Under the condition of unconformable deposition of the Cretaceous Zhidan Group huge thick strata in the Inner Mongolia-Shanxi mining area, frequent occurrence of strong mine earthquake (SME) during deep mining, resulting in tremors at the surface，has severely constrained efficient production at the area. In order to solve the problem of inaccurate source information and unclear stress triggering mechanism, which makes it difficult to prevent and control SME, the working face of a mine in the area where SME occurred frequently is used as a background for the study, based on preliminary detection of stratigraphic rock movement characteristics, the principal component analysis (PCA) was applied to extract the effective components of waveforms, the hybrid moment tensor inversion (HMTI) are used to solve focal mechanism of SME, stress inversion model modified, and stress inversion algorithm optimised, based on the algorithm, solved the distribution characteristics of the stress field before and after the occurrence of SME, introduced instability coefficients to evaluate the stability of the overburden, and analysed the stress triggering mechanism of SME. The results show that the PCA can extract the key information of complex waveforms, and applied to the HMTI can significantly reduce the error between the theoretical and observed amplitudes of waveforms, and ensure the accuracy of the source rupture information used for stress inversion. The improved algorithm meets the requirements of typical tension, compression and composite rupture source, and can reduce the error from 60% to less than 20%, which verifies the reasonableness of the algorithm applied to the complex rupture source stress field inversion in coal mine. Before the occurrence of SME, the maximum principal stress increases significantly compared with other principal stresses, and the direction is approximately vertical, and the deflection of the maximum principal stress plays a controlling role in inducing SME, the fracture of the huge thick strata interacts with the changes in the direction and magnitude of the principal stress, and under the effect of vertical uniaxial compression of the maximum principal stress, the huge thick strata moves violently and instantaneously releases its elastic energy, resulting in the occurrence of SME. The conclusions of the study can provide theoretical support for reducing the frequency of SME by weakening the huge thick strata in terms of stress regulation.